The Concept of Communication in the Quran; Analysis of Theory and Practice - Tanjung, M. Taufiq Hidayah; Abdullah, Abdullah (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
From the analysis conducted on the basic concept of Islamic communication, it can be concluded that Islamic communication is formulated as a process of exchanging messages based on Islamic teachings with the aim of achieving truth, harmony, and the pleasure of Allah. Its principles include honesty (as-sidq), trustworthiness, justice (al-'adalah), wisdom, and moderation (wasatiyyah). These principles guide every aspect of communication to be oriented towards moral and transcendental values, distinguishing it from secular communication which often focuses on pragmatic or materialistic goals. Dakwah communication aims to convey Islamic teachings wisely, wisely, and compassionately, as exemplified by the prophets. Prophetic communication, which emphasizes prophetic qualities such as shiddiq (honest), amanah (trustworthy), tabligh (delivering), and fathanah (intelligent), has high relevance in the modern world. In this context, da'wah and prophetic communication can be applied through social media, education, and interactive dialogue that prioritizes Islamic ethics, so that it is effective in countering disinformation, resolving conflicts, and strengthening harmonious social relations. The main sources of Islamic communication are the Qur'an, Hadith, and other sources such as ijma (consensus of scholars) and qiyas (legal analogy) are the main foundations of Islamic communication. The Qur'an provides moral guidelines and principles of fair and honest communication. Hadith exemplifies the communication practices of the Prophet Muhammad SAW which are full of wisdom and compassion. The relevance of these sources in modern life lies in their ability to be a guide to communication ethics, both in interpersonal relationships and in the use of communication technology.